Cultural Mandate in Business Ethics: Theological Study and Practical Implementation - Ranto, Ranto (Theological Journal Kerugma, 2025)
This research aims to conduct a theological study of the cultural mandate as found in Genesis 1:27-28, to understand its basic concepts and moral-ethical dimensions, and its practical implementation in business ethics. In short, the cultural mandate is a mandate given to humans to care for creation, to cultivate and manage creation in divine management as Imago Dei responsibly. This mandate becomes a fundamental calling for humans to work, create, cultivate, and manage the earth and its contents responsibly before God. This cultural mandate becomes an important and fundamental moral-ethical framework for humans to work on earth, including business practices and activities. However, it has become common knowledge that there have been so many deviations in the management of the earth, including in business activities, resulting in negative impacts. This is where the importance of implementing the important truths of this cultural mandate in the dynamics of work and all business activities lies. This research uses a qualitative descriptive method based on literature data or library sources. Through this method, the researcher intends to qualitatively examine the concept and meaning of the cultural mandate, to explore and discover the moral-ethical aspects and principles within the cultural mandate, and how these are then implemented in business practices, as theological ethics in business practices.